Non-specific colitis among patients with colitis: frequency and relation to inflammatory bowel disease, a prospective study - Emara,Mohamed H. (2019)
Abstract Background and study aim The term non-specific colitis refers to an inflammatory condition of the colon that microscopically lacks the characteristic features of any specific form of colitis and is commonly seen in pathology reports of colonoscopy biopsies. In fact, it has been questioned whether it is a separate pathological entity or it is merely an intermediate stage in the course of inflammatory bowel disease. This study was conducted to estimate the prevalence of non-specific colitis among patients with colitis and characterize its natural history over a 6 months year period. Patients and methods Eighty adult patients presented for colonoscopy were enrolled. In the final analysis they were divided into Group A; the non-specific colitis Group and Group B; the inflammatory bowel disease Group. All patients were subjected to: full history taking, full clinical examination, laboratory investigations: which included stool analysis, CRP, ESR, complete colonoscopy and entire random colon biopsies for histopathological examination. Results Group A included 67 patients (83.75%) while Group B included 13 (16.25%) patients. Patients with IBD had clinical and laboratory features of inflammation significantly higher than patients with non-specific colitis. Six patients (8.95%) of non-specific colitis group developed histologic features of florid inflammatory bowel disease after 6 months. There were no independent predictors of this conversion. Conclusion Among our 80 patients with colonoscopy and biopsy 67 (83.75%) were diagnosed as non-specific colitis and out of them 6 patients (8.95%) were reexamined after 6 months and proved to have inflammtory bowel disese this change was not linked to predictive factors.